2018
DOI: 10.3390/ijms19010175
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis in Haematococcus pluvialis: Astaxanthin Induction by High Light with Acetate and Fe2+

Abstract: Haematococcus pluvialis is a commercial microalga, that produces abundant levels of astaxanthin under stress conditions. Acetate and Fe2+ are reported to be important for astaxanthin accumulation in H. pluvialis. In order to study the synergistic effects of high light stress and these two factors, we obtained transcriptomes for four groups: high light irradiation (HL), addition of 25 mM acetate under high light (HA), addition of 20 μM Fe2+ under high light (HF) and normal green growing cells (HG). Among the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 29 publications
2
27
0
1
Order By: Relevance
“…6 g l −1 ) of NaAc promoted increases in dry weight. The explanation for this pattern might be that the high concentration of NaAc induced algal cells to produce thicker cyst walls as a self-protective mechanism, which might have increased cell mass rather than cell growth (He et al 2018). The effect of NaAc on astaxanthin accumulation is always integrated with increased biomass production (Göksan et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 g l −1 ) of NaAc promoted increases in dry weight. The explanation for this pattern might be that the high concentration of NaAc induced algal cells to produce thicker cyst walls as a self-protective mechanism, which might have increased cell mass rather than cell growth (He et al 2018). The effect of NaAc on astaxanthin accumulation is always integrated with increased biomass production (Göksan et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The cells were cultured with a 12:12 h dark:light cycle at 23 ± 1°C without aeration and shaken 3 to 5 times daily. When the cell concentration reached (4−5) × 10 5 cells ml −1 , they were transferred to an induction culture (He et al 2018), which contained 100 μl FeSO 4 •7H 2 O (0.05 mg l −1 ), 100 μl VB 12 (0.05 mg l −1 ), and 100 ml NaAc (at concentration gradients of 0, 3, 4, 5, and 6 g l −1 ). All of the treatments were conducted in triplicates of 250 ml.…”
Section: Algal Culture Growth Conditions and Naac Inductionmentioning
confidence: 99%
“…Analogously, transcriptome analysis of H. pluvialis revealed that high light intensities impacted the expression of genes involved in the carotenoid biosynthesis pathway, including PDS, crtISO, LcyB, LUT1, LUT5, and ZEP (Gwak et al, 2014;He et al, 2018). When the crtO ketolase gene was overexpressed in H. pluvialis, the accumulation of astaxanthin and other ketocarotenoids was greatly increased (Kim and Portis, 2004).…”
Section: Unraveling the Stress-response Mechanisms Of Microalgaementioning
confidence: 97%
“…To obtain insights into the astaxanthin synthesis mechanism under high light conditions, Gwak et al (2014) used transcriptome analysis and found that beta-carotene hydroxylase (BKT or crtZ), phytoene synthase (PSY), and phytoene desaturase (PDS) were all upregulated in H. pluviali s under high irradiance. Analogously, transcriptome analysis of H. pluviali s revealed that high light intensities impacted the expression of genes involved in the carotenoid biosynthesis pathway, including PDS, crtISO, LcyB, LUT1, LUT5, and ZEP ( Gwak et al, 2014 ; He et al, 2018 ). When the crtO ketolase gene was overexpressed in H. pluviali s, the accumulation of astaxanthin and other ketocarotenoids was greatly increased ( Kim and Portis, 2004 ).…”
Section: Application Of “Omics” Technologiesmentioning
confidence: 99%
“…Actualmente, se conocen diferentes condiciones de estrés como la deficiencia de nutrientes tales como el nitrógeno (Gómez et al, 2019;Ma et al, 2018;Tocquin et al, 2012 ), la intensidad de la luz (Lv et al, 2016), colores de luz (Xi et al, 2016), alta salinidad (Lababpour & Lee, 2006), pH y la presencia de nutrientes orgánicos como acetato de sodio o la combinación cloruro de sodio/acetato de sodio, aumentando el contenido total de carotenoides y el contenido total de astaxantina (Pan-utai et al, 2017;Vidhyavathi et al, 2009). El acetato de sodio ha demostrado ser una fuente importante de carbono para la microalga, mejorando su crecimiento y carotenogénesis, debido a que afecta la ruta de la fotosíntesis (He et al, 2018) y aumenta la expresión del gen BKT, produciendo así mayor cantidad de astaxantina, como lo reportan Wan et al (2014), quienes utilizaron para el cultivo de la microalga H. pluvialis y la producción de astaxantina un fotobiorreactor de 10 Litros con medio NIES-C, usando una concentración 10mM de acetato de sodio como fuente de carbono, luz continua con irradiancia de 25 µmol m -2 s -1 , temperatura de 25 ºC, CO2 4 % y pH 7,5, obteniendo una producción de astaxantina de 65,8 mg y una producción de biomasa de 3,7 mg durante 12 días de experimentación. Así mismo, Park et al (2014) reportaron un aumento de la producción de astaxantina utilizando un cultivo mixotrófico combinando acetato de sodio y alta irradiancia, obteniendo una producción de astaxantina de 602 mg/L.…”
Section: Introductionunclassified